The legal grounds of tariff regulation for railway transportation of goods in the Republic of Poland - V. Mushenok; T. Gurzhii; A. Gurzhii (Науковий вісник Ужгородського національного університету. Серія Право)
The article revolves around legal and organizational aspects of tariff regulation for freight rail transport in the Republic of Poland. A detailed characterization of the Polish legislation on tariff regulation of freight transportation by rail was carried out. Its correlation with the requirements of the Directive 2012/34/EU of the European Parliament and of the Council of 21 November 2012 Establishing a single European railway area is highlighted.